A novel fluorescent probe for selective detection of hydrogen sulfide in living cells. (8th March 2018) - Peng, Siqi; Zhong, Tianya; Guo, Tiantong; Shu, Dehua; Meng, Defen; Liu, Haoran; Guo, Dongcai
Abstract : A low cytotoxicity probe for the sensitive detection of endogenous H2 S. Abstract : A novel fluorescent probe for the detection of H2 S in living cells was designed and synthesized by introducing 2, 4-dinitrophenyl ether into a phenanthroimidazole derivative. The structures of the fluorophore and the probe were characterized using 1 H NMR, 13 C NMR and mass spectra. The probe shows excellent sensitivity, and the detection limit is 1.11 μM. High selectivity and competition are also revealed in corresponding studies. The probe can be applied in a wide pH range. Cellular assays indicate that the cytotoxicity of the probe is low, and the cellular permeability is good. With these desirable properties, the probe demonstrates a possible approach for investigating the biological roles of H2 S in living tissues.